The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1121/1.4976327
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the binaural contribution to speech-in-noise reception in elderly hearing-impaired listeners

Abstract: To scrutinize the binaural contribution to speech-in-noise reception, four groups of elderly participants with or without audiometric asymmetry <2 kHz and with or without near-normal binaural intelligibility level difference (BILD) completed tests of monaural and binaural phase sensitivity as well as cognitive function. Groups did not differ in age, overall degree of hearing loss, or cognitive function. Analyses revealed an influence of BILD status but not audiometric asymmetry on monaural phase sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…It would be useful in future studies to assess how well the test works for people with asymmetric losses. Neher (2017) measured BMLDs for listeners with both symmetric and asymmetric hearing loss at low frequencies and found no significant effect of asymmetry, suggesting that binaural TFS processing was still possible for the asymmetric group. If so, then we would expect the TFS-AF test also to be applicable to listeners with asymmetric hearing loss.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It would be useful in future studies to assess how well the test works for people with asymmetric losses. Neher (2017) measured BMLDs for listeners with both symmetric and asymmetric hearing loss at low frequencies and found no significant effect of asymmetry, suggesting that binaural TFS processing was still possible for the asymmetric group. If so, then we would expect the TFS-AF test also to be applicable to listeners with asymmetric hearing loss.…”
Section: Discussionmentioning
confidence: 97%
“…Another commonly used measure of binaural TFS sensitivity is the binaural masking level difference (BMLD; e.g., Neher, 2017 ; Santurette & Dau, 2012 ). The BMLD requires two threshold measurements (e.g., N 0 S 0 and N 0 S π ), although the N 0 S π threshold alone has sometimes been used as an estimate of binaural TFS sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…This was done to follow the audiometric inclusion criterion of symmetric hearing sensitivity used in most (but not all) previous studies investigating binaural TFS sensitivity. Neher (2017) reported that there were no differences in binaural TFS sensitivity between listeners with symmetric and asymmetric hearing losses at low frequencies. However, his study assessed BMLDs (and not IPD discrimination) and hence it was deemed prudent to exclude the few asymmetric cases observed in some data sets from the meta-analysis.…”
Section: Methodsmentioning
confidence: 97%
“…Binaural TFS sensitivity has been studied using a variety of behavioral tasks, such as the binaural masking level difference (BMLD; e.g., Neher, 2017 ; Pichora-Fuller & Schneider, 1991 ; Santurette & Dau, 2012 ; Strelcyk & Dau, 2009 ), interaural time difference (ITD) discrimination (e.g., Füllgrabe & Moore, 2014 ; Strouse, Ashmead, Ohde, & Grantham, 1998 ), and IPD discrimination (e.g., Füllgrabe, Harland, Sęk, & Moore, 2017 ; Ross et al., 2007 ; Strelcyk & Dau, 2009 ). One test that has been used in several recent studies is the TFS-LF test developed by Hopkins and Moore (2010) and implemented by Sęk and Moore (2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides the binaural tests presented previously, another approach for evaluating the binaural processing abilities is assessing binaural masking release (Durlach, 1963), which has been used in several studies (Neher, 2017;Strelcyk & Dau, 2009) and implemented in some commercial audiometers (Brown & Musiek, 2013). In this paradigm, a tone-in-noise stimulus is presented in two conditions: (1) a diotic condition where the tone is in phase in the two ears, and (2) a dichotic condition where the tone is in antiphase in the two ears.…”
Section: Binaural Masking Releasementioning
confidence: 99%